2016
DOI: 10.1038/ncomms11600
|View full text |Cite
|
Sign up to set email alerts
|

ATP6AP1 deficiency causes an immunodeficiency with hepatopathy, cognitive impairment and abnormal protein glycosylation

Abstract: The V-ATPase is the main regulator of intra-organellar acidification. Assembly of this complex has extensively been studied in yeast, while limited knowledge exists for man. We identified 11 male patients with hemizygous missense mutations in ATP6AP1, encoding accessory protein Ac45 of the V-ATPase. Homology detection at the level of sequence profiles indicated Ac45 as the long-sought human homologue of yeast V-ATPase assembly factor Voa1. Processed wild-type Ac45, but not its disease mutants, restored V-ATPas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
146
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(153 citation statements)
references
References 64 publications
6
146
1
Order By: Relevance
“…Finally, varying degrees of hypogammaglobulinemia with loss of antibody, are also noted in a number of disease with additional organ, metabolic or developmental defects ( 163 tetratricopeptide repeat domain 37 (TTC37), 164 and ATPase H+ transporting accessory protein 1 (ATP6AP1) deficiency 165 and phospholipase C, gamma-2 (PLCG2). 166…”
Section: Hypogammaglobulinemia With Syndromic Featuresmentioning
confidence: 99%
“…Finally, varying degrees of hypogammaglobulinemia with loss of antibody, are also noted in a number of disease with additional organ, metabolic or developmental defects ( 163 tetratricopeptide repeat domain 37 (TTC37), 164 and ATPase H+ transporting accessory protein 1 (ATP6AP1) deficiency 165 and phospholipase C, gamma-2 (PLCG2). 166…”
Section: Hypogammaglobulinemia With Syndromic Featuresmentioning
confidence: 99%
“…Of note, proteomics studies on purified SVs have also revealed the presence of ATP6AP1 (ATPase H + Transporting Accessory Protein 1, also known as Ac45) and ATP6AP2 (ATPase H + Transporting Accessory Protein 2, also known as the (pro)renin receptor/PRR) . Those two brain‐enriched trans‐membrane proteins are accessory components of the vATPase with some additional cellular functions—for example, ATP6AP1 is involved in the vATPase transport and exocytosis, and ATP6AP2 is reported to be essential for biogenesis of active vATPases . ATP6AP2 is also ideally posed to link vATPase to cell signaling, for example, the renin‐angiotensin system for regulating blood pressure and electrolyte balance, as well as Wnt signaling during embryo development .…”
Section: Mechanisms Of Sv (Re)acidificationmentioning
confidence: 99%
“…Of note, knock‐outs of the essential vATPase subunits are lethal, as well as of accessory subunit ATP6AP1, making the studies of these proteins difficult. If not lethal, a genetic perturbation of the vATPase subunits and accessory proteins ATP6AP1 and ATP6AP2 lead to inherited disorders …”
Section: Regulation Of the Vatpase Activity On The Synaptic Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen patients have been reported with the X‐linked ATP6AP1 deficiency (ATP6AP1‐CDG) . Key features were immunodeficiency and liver involvement .…”
Section: Introductionmentioning
confidence: 99%